Impact of plant matrix polysaccharides on cellulose produced by surface-tethered cellulose synthases. (15th April 2017) - Basu, Snehasish; Omadjela, Okako; Zimmer, Jochen; Catchmark, Jeffrey M.
Highlights: Cellulose is produced by engineered immobilized glycosyltransferases whose product interacts with free polysaccharides forming a composite. Non-cellulosic plant polysaccharides perturb in vitro cellulose II formation, but are not a controlling factor in allomorph formation. Cellulose I did not form in the presence of xyloglucan and glucomannan. Results suggest allomorph formation in plant cellulose is driven principally by synthase organization and not regulated by polysaccharides. Abstract: Surface immobilized BcsA-B cellulose synthases synthesize crystalline cellulose II under in vitro conditions and were used to explore the interaction between cellulose and hemicelluloses and pectin. The morphology of the cellulose microfibrils changed in the presence of xyloglucan and glucomannan, while pectin did not significantly impact morphology. X-ray diffractometry and FT-IR spectroscopy indicated that crystal size and crystallinity were significantly affected by xyloglucan and glucomannan but not altered by pectin. Glucomannan had the most significant impact on the structure of cellulose and inhibits crystallization. The presence of xyloglucan and glucomannan prevents the proper assembly of cellulose microfibrils and changes the crystalline properties of cellulose II in in vitro conditions, but did not have any impact on cellulose allomorph.